Dominant Role of CD80–CD86 Over CD40 and ICOSL in the Massive Polyclonal B Cell Activation Mediated by LATY136F CD4+ T Cells - Chevrier, Stephane; Genton, Celine; Malissen, Bernard; Malissen, Marie; Acha-Orbea, Hans (Frontiers in Immunology, 2012)
Coordinated interactions between T and B cells are crucial for inducing physiological B cell responses. Mutant mice in which tyrosine 136 of LAT is replaced by a phenylalanine (LatY136F) exhibit a strong CD4+ T cell proliferation in the absence of intended immunization. The resulting effector T cells produce high amounts of TH2 cytokines and are extremely efficient at inducing polyclonal B cell activation. As a consequence, these LatY136F mutant mice showed massive germinal centre formations and hypergammaglobulinemia. Here, we analyzed the involvement of different costimulators and their ligands in such T-B interactions both in vitro and in vivo, using blocking antibodies, knockout mice and adoptive transfer experiments. Surprisingly, we showed in vitro that although B cell activation required contact with T cells, CD40 and ICOSL signalling were not necessary for this process. These observations were further confirmed in vivo, where none of these molecules were required for the unfolding of the LAT CD4+ T cell expansion and the subsequent polyclonal B cell activation, although, the absence of CD40 led to a reduction of the follicular B cell response. These results indicate that the crucial functions played by CD40 and ICOSL in germinal centre formation and isotype switching in physiological humoral responses are partly overcome in LatY136F mice. By comparison, the absence of CD80-CD86 was found to almost completely block the in vitro B cell activation mediated by LatY136F CD4+ T cells. The role of CD80-CD86 in T-B cooperation in vivo remained elusive due to the upstream implication of these costimulatory molecules in the expansion of LatY136F CD4+ T cells. Together, our data suggest that CD80 and CD86 costimulators play a key role in the polyclonal B cell activation mediated by LatY136F CD4+ T cells even though additional costimulatory molecules or cytokines are likely to be required in this process.